Community health volunteers’ experiences during the COVID-19 pandemic in Kiambu county, Kenya: A qualitative study - Naomi Wachira; Prabhjot Kaur Juttla; Bernard Kimani; Moses Kamita; Samuel Mungai; James Ndimbii; Francis Makokha; Magoma Mwancha-Kwasa (PLoS ONE, 2025)
Background For already overburdened health systems in low- and middle-income countries (LMICs), the COVID-19 pandemic presented an almost impossible challenge. In Kenya, efforts to mitigate the impact of the pandemic included the mobilization of community health volunteers (CHVs), a cadre that has been historically understaffed and under-resourced. These volunteers were required to sustain the delivery of routine community-based health services while also taking on additional responsibilities related to COVID-19 mitigation. This study explored the challenges faced by CHVs during the COVID-19 response in Kiambu County; focusing on their experiences with control measures, impacts on community-level healthcare delivery, and perspectives on the government’s pandemic response within the community health framework. Methods This study employed a phenomenological exploratory qualitative design. Due to logistical constraints, only two focus group discussions could be conducted with 24 CHVs, representing 48% of eligible participants who met the inclusion criteria: a minimum of five years of experience, active involvement in the pandemic response, and availability for the interview. Data were digitally recorded, transcribed, translated, and coded for thematic analysis. Results Specific themes from the experiences of the CHVs during the COVID-19 lockdown were: (1) dedication and commitment to serving the community; (2) overcoming demoralization; and (3) community barriers to health care delivery and access. In regards to the community perspectives of COVID-19, the CHVs relayed widespread misinformation among community members, with experiences of stigma due to COVID-19 misconceptions. They also gave second-person accounts of the economic strife the community went through as a result of mitigation measures. The CHVs were skeptical in the county’s preparedness in dealing with both the COVID-19 and future pandemics. Conclusion Despite facing stigma, misinformation, limited resources, and economic hardships, CHVs demonstrated commitment to their roles. Their efforts not only underscored their resilience but also revealed critical gaps in preparedness and resource allocation within the healthcare system. However, the small number of FGDs and insufficent data saturation should be considered when interpreting the findings. Nonetheless, our study provides a starting point for further research and comparative analysis across other counties in Kenya.